2017
DOI: 10.1021/acs.energyfuels.7b02945
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Fluid Geodynamics: The Chemistry and Physics of Oilfield Reservoir Fluids after Trap Filling

Abstract: Oilfield reservoirs exhibit a wide array of complexities that have great impact on the efficiency of oil production. Major challenges include delineating overall reservoir architecture and the distributions of the contained fluids. Reservoir crude oils consist of dissolved gases, liquids, and dissolved solids (the asphaltenes); the corresponding compositional variations and phase transitions within reservoirs greatly impact production strategies and economic value. Standard workflows for understanding reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 115 publications
(429 reference statements)
0
21
0
1
Order By: Relevance
“…Key issues that have been addressed include reservoir connectivity , and its inverse compartmentalization, , baffling, , viscous oil and tar mat formation, , upstructure mobile tar, aquifer support, asphaltene onset pressure, , wax precipitation, solution gas gradients, timing of charge, fault block migration, , biogenic gas charge into oil, and spill–fill trap filling, , along with traditional geochemical concerns of biodegradation, ,, gas washing, and water washing. ,, These wide-ranging concerns treated in various RFG oilfield studies establish that the development and application of asphaltene thermodynamics extends far beyond issues that are directly impacted by asphaltenes, such as tar mat formation. Instead, RFG exploits thermodynamics, which itself is unlimited in its applications. ,,, …”
Section: Reservoir Fluid Geodynamics (Rfg)mentioning
confidence: 99%
“…Key issues that have been addressed include reservoir connectivity , and its inverse compartmentalization, , baffling, , viscous oil and tar mat formation, , upstructure mobile tar, aquifer support, asphaltene onset pressure, , wax precipitation, solution gas gradients, timing of charge, fault block migration, , biogenic gas charge into oil, and spill–fill trap filling, , along with traditional geochemical concerns of biodegradation, ,, gas washing, and water washing. ,, These wide-ranging concerns treated in various RFG oilfield studies establish that the development and application of asphaltene thermodynamics extends far beyond issues that are directly impacted by asphaltenes, such as tar mat formation. Instead, RFG exploits thermodynamics, which itself is unlimited in its applications. ,,, …”
Section: Reservoir Fluid Geodynamics (Rfg)mentioning
confidence: 99%
“…An industry-wide study of 28 deepwater Gulf of Mexico reservoirs showed that 75% of the reservoirs underperformed in production rate or total recovery primarily as a result of unrecognized compartmentalization . Many reservoir studies have confirmed that if the reservoir crude oils are in thermodynamic equilibrium, then the reservoir is connected; it takes massive fluid compositional redistribution to equilibrate reservoir fluids, thus requiring connectivity. , In contrast, pressure equilibration among different compartments requires only small mass transport and does not require excellent connectivity in reservoirs. Pressure communication is a necessary but insufficient condition to establish flow communication in reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltene gradients are the most recent reservoir fluid property to be addressed by a proper thermodynamic treatment, and they provide the most stringent test of thermodynamic equilibrium. , Asphaltene gradients can be measured accurately, especially through the use of in situ fluid measurements in oil wells, referred to as “downhole fluid analysis” (DFA) in oilfield well logging . The latest generation of well logging tools that performs DFA can measure fluid gradients accurately and efficiently .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Несмотря на широкое использование высокотехнологичных геофизических методов разведки и современных вычислительных технологий для обработки полученной информации, геологическое строение введенных в эксплуатацию нефтяных месторождений уточняют на основе полученных данных о материальном составе извлекаемых пластовых флюидов [1,2]. Особый интерес проблема детализации геологического строения представляет для эксплуа-тируемых многопластовых месторождений, когда в результате применения интенсивных технологий повышения нефтеизвлечения возможно появление неконтролируемых межпластовых перетоков.…”
unclassified